Association of Physical Activity With Telomere Length Among Elderly Adults - The Oulu Cohort 1945 - Stenbäck, Ville; Mutt, Shivaprakash Jagalur; Leppäluoto, Juhani; Gagnon, Dominique D.; Mäkelä, Kari A.; Jokelainen, Jari; Keinänen-Kiukaanniemi, Sirkka; Herzig, Karl-Heinz (Frontiers in Physiology, 2019)
Introduction: Physical activity (PA) has been associated with telomere shortening. The association of PA intensity or volume with telomere length (TL) is nonetheless unclear. The aim of our study was to investigate the associations of exercise intensity and volume with TL in elderly adults from Northern Finland (65° latitude North). Methods: Seven hundred elderly subjects born in 1945 in the Oulu region were investigated. PA was measured during a 2-week period with a wrist-worn accelerometer. In addition, a questionnaire was used to assess sedentary time and to achieve a longitudinal PA history and intensity. Relative telomere lengths (RTL) were determined from frozen whole blood samples using a qPCR-based method. Results: Relative telomere lengths were significantly longer in women than men and negatively correlated with age in both genders (men r = -0.210, p = 0.000, women r = -0.174, and p = 0.000). During the 2-week study period, women took more steps than men (p = 0.001), but the association between steps and RTL was only seen in men (p = 0.05). Total steps taken (r = 0.202 and p = 0.04) and sedentary time (r = -0.247 and p = 0.007) significantly correlated with RTLs in 70-year old subjects. Moderate PA was associated with RTL in subjects with the highest quartile of moderate PA compared to the three lower quartiles (p-values: 0.023 between 4th and 1st, 0.04 between 4th and 2nd, and 0.027 between 4th and 3rd) in the 70-year old subjects. Conclusion: Women had longer RTL and a higher step count compared to men. However, exercise volume and RTL correlated positively only in men. Surprisingly, age correlated negatively with RTL already within an age difference of 2 years. This suggests that telomere attrition rate may accelerate in older age. Moderate physical activity at the time of study was associated with RTL.